Influenza vaccination situation in Middle-East and North Africa countries: Report of the 7th MENA Influenza Stakeholders Network (MENA-ISN) - Salah Al Awaidi; Suleiman Abusrewil; Muslim AbuHasan; Meral Akcay; Fatma N.B. Aksakal; Uzma Bashir; Omar Elahmer; Abdoulreza Esteghamati; Milad Gahwagi; Yusuf K. Mirza; Cindy Grasso; George Kassianos; et al. (Elsevier, 2018)
Background: The Middle East and North Africa (MENA) region faces a dual challenge with regard to influenza infection due to severe zoonotic influenza outbreaks episodes and the circulation of Northern Hemisphere human influenza viruses among pilgrims. Methods: The MENA Influenza Stakeholder Network (MENA-ISN) was set-up with the aim of increasing seasonal influenza vaccination coverage by (i) enhancing evidence-based exchanges, and (ii) increasing awareness on the safety and benefits of seasonal vaccination. During the 7th MENA-ISN meeting, representatives from 8 countries presented their influenza surveillance, vaccination coverage and actions achieved and provided a list of country objectives for the upcoming 3 years. Results: MENA-ISN countries share the goal to reduce influenza related morbidity and mortality. Participants admitted that lack of knowledge about influenza, its consequences in terms of morbidity, mortality and economy are the major barrier to attaining higher influenza vaccination coverage in their countries. The cost of the vaccine is another key barrier that could contribute to low vaccination coverage. Participants drew a list of strategic interventions to bridge gaps in the knowledge of influenza burden in this region. Conclusions: Participating countries concluded that despite an increase in vaccine uptake observed during the last few years, influenza vaccination coverage remains relatively low. Priority areas should be identified and action plans tailored to each country situation set-up to investigate the best way to move forward. Keywords: Influenza, Vaccination coverage, Surveillance, Middle East and North Africa